Determining Vaccine Justice in the Time of COVID-19: A Democratic Perspective. Issue 3 (2022) - Tanasoca, Ana; Dryzek, John S.
Abstract: What does vaccine justice require at the domestic and global levels? In this essay, using the COVID-19 pandemic as a backdrop, we argue that deliberative-democratic participation is needed to answer this question. To be effective on the ground, abstract principles of vaccine justice need to be further specified through policy. Any vaccination strategy needs to find ways to prioritize conflicting moral claims to vaccine allocation, clarify the grounds on which low-risk people are being asked to vaccinate, and reach a balance between special duties toward countrymen and universal duties toward foreigners. Reasonable moral disagreement on these questions is bound to exist in any community. But such disagreement threatens to undermine vaccine justice insofar as the chosen vaccination strategy (and its proposed specification of vaccine justice) lacks public justification. Inclusive democratic deliberation about vaccine justice is a good mechanism for tackling such moral disagreement. By allowing residents and citizens to participate in the specification of abstract principles of vaccine justice, and their translation into policy, democratic deliberation can enhance the legitimacy of any vaccination strategy and boost compliance with it.